Spanish version of the Santa Clara Brief Compassion Scale: evidence of validity and factorial invariance in Peru - Caycho-Rodríguez, Tomás (2020)
The Santa Clara Brief Compassion Scale (SCBCS) is a brief measure of compassion, created in English and translated into Brazilian Portuguese. Nonetheless, to date, no study has assessed the psychometric evidence of its Spanish translation. This study examines the evidence of validity, reliability, and factorial invariance according to the gender of a Spanish version of the SCBCS. Participants included 273 Peruvian university students (50.9% women) with an average age of 21.23 years (SD = 3.24); divided into two groups of men and women to conduct the invariance factor analysis. Other measures of mindfulness, well-being, empathy, and anxiety were applied along with the SCBCS. The Confirmatory Factor Analysis (CFA) indicated that a unifactorial model adjusted significantly to the data (χ2 = 12,127, df = 5, p =.033, χ2 /df = 2.42, CFI =.998, RMSEA =.072 [CI90%.019,.125]; SRMR =.030, WRMR =.551) and presented good reliability (α =.90 [95%.88–.92]; ω =.91). Moreover, correlations between the SCBCS and other measures of mindfulness (r =.53, p <.05, cognitive empathy (r = 55; p <.05), affective empathy (r =.56, p <.05), well-being (r =.55, p <.05), and anxiety (r = −.46; p <.05) supported the convergent and discriminant validity. Likewise, the multiple-group CFA supported the factorial invariance according to the gender of the SCBCS. Results indicate that the SCBCS possesses evidence of validity, reliability, and invariance between men and women for measuring compassion toward others in Peruvian undergraduate students. SCBCS is expected to be used by researchers, healthcare professionals, teachers, and others as a useful measure of compassion in college students.